Зміст форм діяльності відділів прикордонної служби - Ляшук, Р. М.; Ляшук, Р. М.; Ljashuk, R. (My University, 2013)
The article deals with the content of forms of border service division. Due to research regulations and scientific papers identified components form parts of the border service.
Ляшук Р. М. Зміст форм діяльності відділів прикордонної служби / Р. М. Ляшук // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 397-407.
Keywords: відділи прикордонної служби; зміст форм діяльності відділів прикордонної служби; складові форм діяльності відділів прикордонної служби; отделы пограничной службы; содержание форм деятельности отделов пограничной службы; составляющие форм деятельности отделов пограничной службы; border service departments; the content of the forms of activity of departments Border Service; constitute a form of activity of departments Border Service